Sementes de alface biofortificada submetidas ao condicionamento fisiológico, secagem, tolerância a termoinibição e armazenamento - Neves, Flávia de Oliveira Borges Costa (2023)
Physiological conditioning or “priming” is a set of techniques that improve the quality and performance of batches of seeds and/or plants produced, mainly under stress conditions. The thermoinhibition of germination in lettuce seeds causes significant losses for producers, who do not supply thermotolerant commercial cultivars. Information regarding the period in which conditioning remains viable after drying, storage and allows germination of lettuce seeds at high temperatures is incipient. The objective of this work was to analyze the tolerance to thermoinhibition of seeds from biofortified lettuce lines after being subjected to physiological conditioning, drying methods and different storage periods. Seeds of ten genotypes from the UFU Biofortified Lettuce Genetic Improvement Program were produced, in addition to the cultivars Everglades (tolerant to thermoinhibition) and Grand Rapids (sensitive to thermoinhibition). In the first test, the seeds were subjected to physiological conditioning with subsequent storage for 0, 30, 60 days. The physiological aspects of germination and tolerance to thermoinhibition were evaluated at temperatures of 20ºC and 35ºC, in a 12 x 3 x 2 factorial scheme (12 genotypes x 3 storage periods x 2 temperatures). In the second test, the seeds were physiologically conditioned and subsequently subjected to different drying treatments: control (seeds without conditioning - Test); conditioned and non-drying sensations (Cond); smooth slow (SL); quick drying (SR); thermal shock + slow (CTSL); thermal shock + quick dry (CTSR); water content reduction + slow (rSL); and reduced water content + rapid drying (rSR) with storage for 0, 30 and 60 days. The physiological quality of sensations was evaluated and tolerance to thermoinhibition (20ºC and 35ºC) was verified. The second trial was analyzed in an 8 x 3 x 2 factorial scheme (drying methods x storage periods x temperature). UFU125#1#1#1 biofortified lettuce seeds are tolerant to thermoinhibition after physiological conditioning and the effects are maintained in storage. There is a reduction in the physiological quality and thermoinhibition tolerance of seeds from other genotypes, after physiological conditioning and storage. After storage, there is increased mortality and lower germination synchrony in seeds conditioned from biofortified lettuce genotypes at temperatures of 35ºC. Drying of conditioned lettuce seeds should preferably be carried out slowly, with or without reducing the initial water content, to maintain tolerance to thermoinhibition during storage.